Learning through art: decision-making in a complex domain - Koch, Renée Lesley (My University, 2021)
In its most generative form, arts education aims to provide opportunities for learners to develop self-efficacy in cultural practices. While the curriculum espouses values such as creative and critical thinking, it imposes a fixed model of ‘art’, derived from European culture, on all learners. This is both unjust and inadequate. Such a model fails to account for the diverse ways people make meaning of experience and neglects the emergent nature of creative processes. Consequently, learners and teachers need better ways of collaborating to create and recognise value in practices, across boundaries established by culture and convention. Against this background, I set out to 1) construct a model of decision-making in contexts where there are no right answers; 2) gauge Visual Arts learners’ awareness of the range of decision-making strategies and resources available to them, as becoming artists; 3) identify institutional constraints acting on learners’ decision-making within the process of making art; and 4) recommend strategies that learners and teachers can apply, as they work together to create and recognise value in unfamiliar and emergent cultural processes. To achieve these aims, I drew on trans-disciplinary research into agent-centred decision-making which I read through my teaching and creative practices. I developed a conceptual model of decision-making in the process of making art and used this to design a study into learners’ arts-based decisions. For this study, I used a complexity theory-informed methodology and SenseMaker, a narrative-based sense-making tool (app), to gather learners’ self-indexed narratives about decisions they made in the process of making art. I read the findings of this study and those arising from my own practice-based decision-making, through each other. While the model of agent-centred decision-making I developed foregrounds social learning systems, collaboration, elaboration on prior mental models, and the integration of body-brain processes, I found that participants’ self-indexed narratives revealed their decision-making processes to be individualistic, based on a fixed view of knowledge and lacking in awareness of embodied knowledge. These patterns can be linked to systemic constraints in arts education and education, generally, such as the marketisation of learning, graded assessment, and the erasure of the body from learning contexts, through discipline. Drawing on complex adaptive systems theory, I propose approaches to intervention with practical small-scale and safe-to-fail examples
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Doctor of Philosophy, 2021